Pengaruh Tenaga Kerja, Indeks Pembangunan Manusia dan Upah Minimum terhadap Kemiskinan dengan Zakat sebagai Variabel Moderasi di Provinsi Jawa Tengah Tahun 2017-2020 - Alfa Latifatur Rifa; Agus Waluyo (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2023)
Abstract— This research is a quantitative study that aims to determine the effect of labor, human development index and minimum wage on poverty with zakat as a moderating variable. This study uses panel data with a sample of 35 districts/cities and an observation period from 2017 to 2020. The analytical method used is multiple regression analysis with the Moderate Regression Analysis (MRA) test with statistical tools in the form of Eviews 9. The results of this study show that partially the workforce has a positive and insignificant effect on poverty, the human development index has a negative and significant effect on poverty and the minimum wage has a negative and significant effect on poverty. MRA test results show that zakat cannot moderate labor, human development index, and minimum wages on poverty. Keywords—: Manpower; Human Development Index; Minimum Wage; Zakat; Poverty.